The implementation of scenario planning approach in the volatile market: the case of the Russian insurance industry. - Alferova, Olga (2015)
Scenario-based planning strategy is a highly complicated process which has become a new powerful tool allowing to construct the future strategy in the constantly changing environment. However, nowadays not only small companies, but big organisations as well do not use scenario planning efficiently. Another serious constraint in terms of implementation of scenario-based approach is a volatility in the market. The main research task is to investigate how scenarios’ activities, applications and examples could be implemented in the volatile insurance market in Russia. Using the best experience of scenario pioneers and the practice approach the research illustrates possible solutions and tools for successful implementation of scenario planning strategy. Moreover, the paper concentrates on the difference in approaches between organisations operating in the Russian insurance market and the regulators’ strategy. In the findings chapter the research looks into three subthemes: internal managers’ point of view, external specialists in the market vision and finally the regulator’s strategy. As a result, it identifies current market conditions affecting the performance of industry players, critiques of scenario planning in the Russian insurance companies and the role of Regulators in the market. This research identifies the main problems of scenario planning in the volatile market and the gap between companies and regulators’ strategy and demonstrates how important is to look closer at needed activities during scenario planning. Described approaches allow to implement scenario planning activities step by step even in the volatile market. The integration of scenarios and actions is the fundamental and the most difficult part of this cycle. The results of the findings reflect to the current market trends and bring additional advantages for the research. Moreover, it discovers an interconnection between market conditions and strategy development. The lack of competence and strategic thinking among the top managers of insurance companies also affected the market. The volatility in the market is a constraint in the way of scenario thinking strategy. However, the company, whatever its culture is, benefits from more robust planning and continuously improvement in the way of implementation of scenario thinking environment.